Smart multi-project scheduling and multi-skilled workforce assignment for prefabricated bathroom unit production - Han, Jinchi (2024)
This paper addresses low worker productivity in Prefabricated Bathroom Unit (PBU) production. To improve, a hierarchical two-level model is developed to (1) integrate project scheduling and task assignments, (2) incorporate multi-skilled workers at an individual level with heterogeneous skill scopes and levels, and (3) monitor variable processing times influenced by human learning effects. The paper introduces a hybrid whale optimization algorithm (HWOA) to optimize and validate the solution through comparative and sensitivity analysis based on a real-world industrial case. Results show that the proposed algorithm outperforms the classical whale optimization algorithm (WOA) and genetic algorithm (GA) in terms of efficiency, solution quality, and robustness. The paper (1) fills the gap of oversimplified assumptions in precast production scheduling and task assignment, (2) potentially helps precast factory managers plan effectively to maximize productivity, also (3) suggests future research integrating logistics costs and worker fatigue to enhance the model's applicability and accuracy.